In a New York minute - Spencer, Kate, 1979- (Forever, 2022)
"When Franny meets Hayes, it's the opposite of a meet-cute-she's just been laid off, and her dress is caught in the subway doors. As if her day could get any worse, the flimsy fabric rips, and she's left in the hipster equivalent of a hospital gown. Hayes is the stuffy suit who offers to give Franny his coat-alongside an unwelcome zing of attraction. He may have saved her from showing her butt to (more of) the city, but that one act is his only redeeming quality. Franny is eager to forget the whole embarrassing encounter. But thanks to a fellow rider liveblogging the whole incident, Franny and Hayes are NYC's new favorite love story with their very own hashtag: #SubwayQTs. While Franny is quick to dismiss Hayes as just another rich guy, whose nicest assets are hanging in his closet, she's forced to re-evaluate her opinion when their paths keep crossing. Both are desperate to move past their fifteen minutes of fame-enough so for the one-time "subway baes" to form a grudging alliance. But the more time they (reluctantly) spend together, the more Franny begins to wonder if the line between love and hate is just a subway stop away..."--